Mortality and Disease Burden of Injuries from 2008 to 2017 in Anhui Province, China. (22nd April 2020) - Xing, Xiu-Ya; Wang, Peng; Xu, Zhiwei; He, Qin; Li, Rui; Chen, Ye-Ji; Liu, Li-Na; Mao, Yan-Mei; Zhao, Chan-Na; Dan, Yi-Lin; Wu, Qian; Pan, Hai-Feng; et al.
Abstract : Objective . To investigate the temporal trends in mortality and disease burden of injuries in Anhui province from 2008 to 2017, so as to provide reference for injury control and prevention. Methods . Data of mortality were collected from 9 national surveillance points in Anhui province during 2008-2017 in the Information System for Death Cause Register and Management. The surveillance data were analyzed by using crude mortality, standardized mortality rate (SMR), potential year of life lost (PYLL), PYLL rate (PYLLR), and average of year life lost (AYLL). Results . There were a total of 44855 people died from injury, accounted for 9.44% of the all-cause mortality, ranked as the fifth leading cause of deaths in the whole population, and denoted the first leading cause of deaths in the 0-44 year's group. The leading causes of injury deaths were road traffic accidents, suicide, accidental falls, drowning, and poisoning. Road traffic accidents was the primary cause of injury deaths among the male population, while suicide was the dominate cause of injury deaths among the female population. Drowning, traffic accidents, and suicide accounted for the most injury deaths among the population aged 0-14 years, 15-64 years, and above 60 years, respectively. The road traffic accidents accounted for the largest proportion of injury PYLL and PYLLR, and drowning caused the highest AYLL among injury deaths. Conclusion . In Anhui province, road traffic accidents, suicide, accidental falls, drowning, and poisoning were the top five causes of injury deaths that harm the health of local residents; corresponding injury prevention strategies should be formulated.